Seeking the supernatural: the Interactive Religious Experience Model - Leeuwen, Neil Van (Religion, brain & behavior, 2019)
We develop a new model of how human agency-detection capacities and other socio-cognitive biases are involved in forming religious beliefs. Crucially, we distinguish general religious beliefs (such as God exists) from personal religious beliefs that directly refer to the agent holding the belief or to her peripersonal time and space (such as God appeared to me last night). On our model, people acquire general religious beliefs mostly from their surrounding culture; however, people use agency-intuitions and other low-level experiences to form personal religious beliefs. We call our model the Interactive Religious Experience Model (IREM). IREM inverts received versions of Hyperactive Agency-Detection Device Theory (HADD Theory): instead of saying that agency-intuitions are major causes of religious belief in general, IREM says that general belief in supernatural agents causes people to seek situations that trigger agency-intuitions and other experiences, since these enable one to form personal beliefs about those agents. In addition to developing this model, we (1) present empirical and conceptual difficulties with received versions of HADD Theory, (2) explain how IREM incorporates philosophical work on indexical belief, (3) relate IREM to existing anthropological and psychological research, and (4) propose future empirical research programs based on IREM.